ANALYSIS THE EFFECT OF SERVICE QUALITY, PRICE ADVANTAGES, AND MARKETER’S BEHAVIORAL TOWARDS CUSTOMER SATISFACTION IN ORDER TO INCREASE CUSTOMER LOYALTY (Study in PT. DES TEKNOLOGI INFORMASI) - Nugroho, Edwin Krisna (Master of Management Diponegoro University, 2018)
This research is aimed to examine the effect of Service Quality, Price Excellence, and Marketers Behavioral Behavior, to Customer Satisfaction, and its impact on Customer Loyalty. The problem of research is how to improve Customer Loyalty, by improving Customer Satisfaction, through Service Quality, Price Excellence, and Behavior Ethics of Marketers?The sample in this research is the customer of PT. DES Teknologi Informasi of 150 respondents. Data analysis is done by Structural Equation Modeling (SEM) using AMOS software. The results of the analysis show that Service Quality, Price Excellence, Marketers Behavior Ethics, have a positive and significant influence on Service User Satisfaction, in order to increase Service User Loyalty.The results of these empirical studies have an indication that Service Quality has a positive influence on Customer Satisfaction; Price advantage has a positive effect on Customer Satisfaction; Behavior Ethics Marketers have a positive influence on Customer Satisfaction; User Service Satisfaction has a positive effect on Customer Loyalty.